Management of a maxillectomy patient by definitive obturator - Nafij Bin Jamayet (2018)
Background: Prosthetic and surgical procedure can be applied to rehabilitate acquired palatal defect. The obturator prosthesis as a part of prosthetic management are used for separation of oral and nasal cavities to allow adequate deglutition and articulation, support for the soft tissue to restore the midfacial contour in palatal defect cases. Clinical presentation: This clinical report describes a prosthetic approach to the rehabilitation of acquired palatal defect with definitive obturator prosthesis and its outcome. We set the artificial teeth in unilateral group function occlusal scheme and finally process the denture. Conclusion: Rehabilitation with obturator prosthesis is functional, reliable/safe, and easy to build. © 2013 Japan International Cultural Exchange Foundation & Japan Health Sciences University.